Cytotoxic Screening of Plant extracts and Angiogenesis: A Landmark approach to cancer - Chavhan, A.R. (International Journal of Pharmaceutical & Biological Archive, 2010)
Andrographis paniculata and Aegle marmelos are the important medicinal plants. In the Indian Systems of Medicine, they are used against blood cancer, as an analgesic, antithrombotic, thrombolytic, hypoglycemic and antipyretic, antidote for snake venom, diarrhea and constipation. The major objective of this study is to evaluate cytotoxicity of this medicinal plants with help of MTT and Trypan Blue Assay. Angiogenesis model plays an important role to introduce to vascularisation process that plays an important role to focus on organogenesis and to study antiangiogenesis effect of different drugs. The study of angiogenesis is making a profound impact on the biological and medical world. The hope of being able to build new, functional, and durable blood vessels in ischemic tissues, or conversely, to prevent their further growth in malignant and inflamed tissues is becoming more realistic every day. Conc. are prepared of each plant extracts which are 100 µg/ml, 10 µg/ml , 0.1 µg/ml, 0.01 µg/ml and 5-10×10 3 cells/ml are taken into each well which are exposed to different conc. of plant extracts for 96 hr and then treated with MTT and Typan Blue Dye with in 1 hr- 24 hr. For MTT absorbance taken at 570 nm. From IC50 values of MTT assay and percentage of cell viability from trypan Blue Assay of kalmegh for MCF7,A549, DU145 is less as compare to bael fruit for same cell lines, from this it may concluded that Bael Fruit shows potent cytotoxicity than Kalmegh for respective cell lines Angiogenesis was only implicated in number of diseases, such as, cancer, arthritis, and psoriasis. Research in angiogenesis offers a potential to cure a variety of diseases such as Alzheimer’s and AIDS. Modulation of angiogenesis may have an impact on diseases in the twenty-first century similar to that which the discovery of antibiotics had in the twentieth century. Further studies are necessary for chemical characterization of the active principles and more extensive biological evaluations for above cell lines which leads to novel drug innovation.